2003
DOI: 10.1002/anie.200200553
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Hybrids as New Leads for Drug Discovery

Abstract: Natural products play an important role in the development of drugs, especially for the treatment of infections and cancer, as well as immunosuppressive compounds. However, the number of natural products is limited, whereas millions of hybrids as combinations of parts of different natural products can be prepared. This new approach seems to be very promising in the development of leads for both medicinal and agrochemical applications, as the biological activity of several new hybrids exceeds that of the parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
185
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(191 citation statements)
references
References 174 publications
1
185
0
5
Order By: Relevance
“…Among various strategies to improve drug selectivity, conjugation of cytotoxic drug components has proven to be a promising approach to enhance the activity and selectivity of some monomeric leads by forming bivalent heterodimers. 1,2 This concept is now accepted as an effective strategy for designing ligands, inhibitors, and drugs that influence biological systems. On the basis of this theory, some interesting results have been reported by our group as well as others in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Among various strategies to improve drug selectivity, conjugation of cytotoxic drug components has proven to be a promising approach to enhance the activity and selectivity of some monomeric leads by forming bivalent heterodimers. 1,2 This concept is now accepted as an effective strategy for designing ligands, inhibitors, and drugs that influence biological systems. On the basis of this theory, some interesting results have been reported by our group as well as others in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 "In general, the potential of natural product analogues with backbone carbon heteroatom replacements is largely unexplored," said Prof. Altmann, "which is in spite of the fact that such changes could lead to improved synthetic accessibility and offer the potential to generate large sets of diverse analogues in a rather straightforward manner (for example, through acylation reactions or, in the case of nitrogen, reductive aminations). Perhaps more importantly, however, aza-epothilones such as 1 and 2 may be considered as "non-natural" natural products 8 that still retain most of the overall structural characteristics of a natural product, but at the same time are structurally unique, as they are outside of the general scope of nature's biosynthetic machinery for polyketide synthesis." Azathilones 1 and 2 are accessible through ring closure by ring-closing olefin metathesis (RCM); 6 alternatively, 2 has been obtained based on a macrolactonization strategy and construction of the C11-N12 bond through reductive amination.…”
Section: Non-natural Natural Products With Potent Anticancer Activitymentioning
confidence: 99%
“…The features of these new entities often differ from those of the original compounds. Mehta et al 3 and Tietze et al 4 have reported numerous examples of the synthesis of natural products, including steroids, where this concept for the synthesis of new derivatives was utilized. Steroidal conjugates and their pharmacological applications have been discussed by Salunke et al 5 and the use of bile acids as building blocks of supramolecular hosts has been surveyed by Tamminen and Kolehmainen.…”
Section: Introductionmentioning
confidence: 99%